Dynamic slow‐wave interactions in the rabbit small intestine defined using high‐resolution mapping. Issue 9 (27th June 2019) - Cherian Abraham, Ashley; Cheng, Leo K.; Angeli, Timothy R.; Alighaleh, Saeed; Paskaranandavadivel, Niranchan
Abstract: Background: The motility in the small intestine is governed in part by myogenic bio‐electrical events, known as slow waves. High‐resolution multi‐electrode mapping has improved our understanding of slow‐wave propagation in the small intestine but has been applied in a limited number of in vivo animal studies. This study applied high‐resolution mapping to investigate slow waves in the rabbit small intestine. Methods: A high‐resolution flexible printed circuit board array (256 electrodes; 4 mm spacing) was applied in vivo to the rabbit intestine. Extracellular slow‐wave activity was acquired sequentially along the length of the intestine. Key results and conclusions: The majority of the slow waves propagated in the antegrade direction (56%) while retrograde patterns were primarily observed in the distal intestine (29%). Colliding slow‐wave events were observed across the length of the small intestine (15%). The interaction of competing pacemakers was mapped in spatiotemporal detail. The frequency and velocity of the slow waves were highest in the duodenum compared to ileum (20.0 ± 1.2 cpm vs 10.5 ± 0.9 cpm, P  < 0.001; 14.4 ± 3.4 mm/s vs 12.3 ± 3.4 mm/s; P  < 0.05). Inferences: In summary, extracellular serosal slow‐wave activity was quantified spatiotemporally along the length of the rabbit intestine. In particular, the study provides evidence toward the presence and interaction of slow‐wave pacemakers acting along the small intestine and how they may contribute to the slow‐wave frequency gradient along the length of the intestine. Abstract : This study provides evidence toward the presence and interaction of multiple slow‐wave pacemakers in small intestine and how these pacemakers may contribute to the slow‐wave frequency gradient across the length of the intestine.